1999
DOI: 10.1093/oxfordjournals.jbchem.a022414
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Growth Factor Induces the Proliferation, Migration, and Tube Formation of Vascular Endothelial Cells In Vitro, and Angiogenesis In Vivo

Abstract: Connective tissue growth factor (CTGF) is a novel cysteine-rich, secreted protein. Recently, we found that inhibition of the endogenous expression of CTGF by its antisense oligonucleotide and antisense RNA suppresses the proliferation and migration of vascular endothelial cells. In the present study, the following observations demonstrated the angiogenic function of CTGF in vitro and in vivo: (i) purified recombinant CTGF (rCTGF) promoted the adhesion, proliferation and migration of vascular endothelial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
283
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(304 citation statements)
references
References 0 publications
19
283
0
2
Order By: Relevance
“…[17][18][19][20] Increases in expression of u-PAR1, laminin receptor and BMP-1 are consistent with the importance of CTGF and TGF␤1 in tissue repair and remodeling. Bone morphogenetic protein (BMP-1) is identical to procollagen C-proteinase, which cleaves the COOH-propeptides of procollagens I, II and III to yield to major fibrous components of vertebrate extracellular matrix.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…[17][18][19][20] Increases in expression of u-PAR1, laminin receptor and BMP-1 are consistent with the importance of CTGF and TGF␤1 in tissue repair and remodeling. Bone morphogenetic protein (BMP-1) is identical to procollagen C-proteinase, which cleaves the COOH-propeptides of procollagens I, II and III to yield to major fibrous components of vertebrate extracellular matrix.…”
Section: Discussionmentioning
confidence: 60%
“…It has been shown that the expression of u-PAR is required for angiogenesis 23 and both TGF␤1 and CTGF genes are known to induce angiogenesis. 19,20 The observation that u-PAR is expressed in fibrotic fibroblasts and is responsible for cell migration and chemtotaxis, 24,25 which are also known functions of CTGF and TGF␤1, indicates that u-PAR may be induced by CTGF and TGF␤1 in wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…1998;Shimo et al 1999;Kubota and Takigawa 2007a, b. )Similarly,as an angiogenetic factor, VEGF is essential for establishing epiphyseal vascularization (Maes et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is a mitogenic and chemotactic cytokine for ®broblasts (Kothapalli et al, 1997), which provides a rationale for the active role(s) of CTGF in wound healing (Igarashi et al, 1993). Angiogenic activities of CTGF have been disclosed as well by a few independent research groups including ours (Babic et al, 1999;Shimo et al, 1999). The complex and integrated functionality of CTGF is also well-represented in its comprehensive roles in endochondral ossi®cation, most of which have been uncovered in our series of recent studies (Nakanishi et al, 1997;Nishida et al, 1998).…”
Section: Introductionmentioning
confidence: 88%